The AI powered enterprise: a review of cloud computing, web ‎technology and digital marketing - Hadi, Harem; Zeebaree, Subhi R. M. (International Journal of Scientific World, 2025)
The integration of artificial intelligence (AI) into enterprise systems is thoroughly reviewed in ‎this study, with an emphasis on cloud computing, online technologies, and digital marketing. ‎It demonstrates how AI-driven businesses use intelligent automation, real-time analytics, and ‎data-driven decision-making to dramatically increase operational productivity, scalability, and ‎customer engagement. A crucial piece of infrastructure, cloud computing provides the ‎scalable and adaptable resources required for large-scale data processing, AI implementation, ‎and strong cybersecurity. AI-enhanced web technologies, such as intelligent chatbots, ‎recommendation engines, and tailored content, improve user experiences and develop digital ‎interaction techniques. AI in digital marketing greatly improves client interactions and ‎satisfaction by enabling sentiment analysis, predictive analytics, accurate targeting, and ‎campaign automation. Prominent issues, including data privacy, ethical dilemmas, and biases ‎in AI systems, are also covered in the paper.